A pH‐responsive carboxymethyl dextran‐based conjugate as a carrier of docetaxel for cancer therapy. Issue 4 (21st December 2015) - Han, Hwa Seung; Lee, Minchang; An, Jae Yoon; Son, Soyoung; Ko, Hyewon; Lee, Hansang; Chae, Yee Soo; Kang, Young Mo; Park, Jae Hyung
Abstract: Although docetaxel is available for the treatment of various cancers, its clinical applications are limited by its poor water solubility and toxicity to normal cells, resulting in severe adverse effects. In this study, we synthesized a polymeric conjugate with an acid‐labile ester linkage, consisting of carboxymethyl dextran (CMD) and docetaxel (DTX), as a potential anticancer drug delivery system. The conjugate exhibited sustained release of DTX in physiological buffer (pH 7.4), whereas its release rate increased remarkably under mildly acidic conditions (pH < 6.5), mimicking the intracellular environment. Cytotoxicity tests conducted in vitro demonstrated that the conjugate exhibited much higher toxicity to cancer cells under mildly acidic conditions than at physiological buffer (pH 7.4). These results implied that the ester linkage in the conjugate allowed for selective release of biologically active DTX under mildly acidic conditions. The in vivo biodistribution of a Cy5.5‐labeled conjugate was observed using the noninvasive optical imaging technique after its systemic administration into tumor‐bearing mice. The conjugate was effectively accumulated into the tumor site, which may have been because of an enhanced permeability and retention effect. In addition, in vivo antitumor efficacy of the conjugate was significantly higher than that of free DTX. Overall, the CMD‐based conjugate might have promising potential as a carrier of DTX for cancer therapy. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 789–796, 2016.